Optimized Enrichment of Phosphoproteomes by Fe-IMAC Column Chromatography - Ruprecht, Benjamin; Koch, Heiner; Domasinska, Petra; Frejno, Martin; Kuster, Bernhard; Lemeer, Simone (Methods in molecular biology (Clifton, N.J.), 2017)
Phosphorylation is among the most important post-translational modifications of proteins and has numerous regulatory functions across all domains of life. However, phosphorylation is often substoichiometric, requiring selective and sensitive methods to enrich phosphorylated peptides from complex cellular digests. Various methods have been devised for this purpose and we have recently described a Fe-IMAC HPLC column chromatography setup which is capable of comprehensive, reproducible, and selective enrichment of phosphopeptides out of complex peptide mixtures. In contrast to other formats such as StageTips or batch incubations using TiO2 or Ti-IMAC beads, Fe-IMAC HPLC columns do not suffer from issues regarding incomplete phosphopeptide binding or elution and enrichment efficiency scales linearly with the amount of starting material. Here, we provide a step-by-step protocol for the entire phosphopeptide enrichment procedure including sample preparation (lysis, digestion, desalting), Fe-IMAC column chromatography (column setup, operation, charging), measurement by LC-MS/MS (nHPLC gradient, MS parameters) and data analysis (MaxQuant). To increase throughput, we have optimized several key steps such as the gradient time of the Fe-IMAC separation (15 min per enrichment), the number of consecutive enrichments possible between two chargings (>20) and the column recharging itself (<1 h). We show that the application of this protocol enables the selective (>90 %) identification of more than 10,000 unique phosphopeptides from 1 mg of HeLa digest within 2 h of measurement time (Q Exactive Plus).
Keywords: LC-MS; statistika jako téma; Cell Line; proteomika; Phosphocapture; Phosphoproteins; Phosphorylation; fosfoproteiny; Statistics as Topic; železo; fosfopeptidy; Iron; Proteomics; Proteome; Humans; Phosphopeptides; Tandem Mass Spectrometry; Software; chromatografie kapalinová; imidazoly; tandemová hmotnostní spektrometrie; buněčné linie; proteom; software; Chromatography, Liquid; Imidazoles; lidé; Workflow; průběh práce